The Development of Smart Parcel Receiver Box - Mohd Tahyuddin, Nur Aqiela Shahira; Ab Rahman, Azmanirah; Subramaniam, Tamil Selvan; Muhamed Yusof, Anizam (Research and Innovation in Technical and Vocational Education and Training, 2021)
Abstract: Online shopping has become a new trend shopping recently. However, the recipient is often not at home when the items are delivered. This study aims to design, develop, and evaluate a Smart Parcel Receiver Box. The goal of this study is to help recipients keep their packages safe during delivery time. The researcher has used the Engineering Design Project (EDP). EDP includes 5 phases: identification of the problem, analysis of the problem, brainstorming alternative design, modelling the best solution, refinement and retesting the model. To open the box, the sender should ask permission from the receiver by scanning the QR code displayed on the box door. The receiver will permit it by unlocking the door of the box remotely using apps, namely web pages. Overall, the project achieved the objectives of the study. However, there is still space for improvement in terms of product design and apps used. Keywords: Smart Parcel Receiver Box, Engineering Design Process Model, Web page, QR codes